2013
DOI: 10.1117/12.2027253
|View full text |Cite
|
Sign up to set email alerts
|

In vivophotoacoustic imaging of breast cancer tumor with HER2-targeted nanodiamonds

Abstract: Radiation-damaged nanodiamonds (NDs) are ideal optical contrast agents for photoacoustic (PA) imaging in biological tissues due to their good biocompatibility and high optical absorbance in the near-infrared (NIR) range. Acid treated NDs are oxidized to form carboxyl groups on the surface, functionalized with polyethylene glycol (PEG) and human epidermal growth factor receptor 2 (HER2) targeting ligand for breast cancer tumor imaging. Because of the specific binding of the ligand conjugated NDs to the HER2-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, for in vivo imaging aimed as a medical diagnostic of said lesions, NIR-emitting F-NDPs would likely be more advantageous. 11,13 The innate ability of NIR light to penetrate biological tissues with limited interference from endogenous fluorophores has already been demonstrated in studies where certain elements of blood clots, such as fibrin, were detected in vivo. 12 The NIR technology is expected to afford extracorporeal, telemetry-based, "on line" assessment of blood clots using ambulatory facilities for the accurate, large-scale assessment of cardiovascular risk of TEE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for in vivo imaging aimed as a medical diagnostic of said lesions, NIR-emitting F-NDPs would likely be more advantageous. 11,13 The innate ability of NIR light to penetrate biological tissues with limited interference from endogenous fluorophores has already been demonstrated in studies where certain elements of blood clots, such as fibrin, were detected in vivo. 12 The NIR technology is expected to afford extracorporeal, telemetry-based, "on line" assessment of blood clots using ambulatory facilities for the accurate, large-scale assessment of cardiovascular risk of TEE.…”
Section: Discussionmentioning
confidence: 99%
“…4 Of particular interest are carbon-based particles, such as nanodiamond particles (NDPs), which have been functionalized for diverse applications, 5 such as drug discovery, [6][7][8] drug delivery, 9,10 and imaging of pathological sites in vivo. 9,[11][12][13] More recently, special attention is focused on NDPs that can be excited optically to emit fluorescent light (F-NDPs) at various wavelengths, especially in the near infrared (NIR) range. 11,12 The innate ability of these new-generation NIR-emitting F-NDPs to report from within biological tissues with limited interference from endogenous fluorophores has already been demonstrated in studies, where certain elements of blood clots, such as fibrin, were detected in vivo.…”
mentioning
confidence: 99%
“…72 With respect to the development of TCA for PA imaging, a number of exciting studies have been reported targeting various members of the ErbB family. 16,17,53,73–84…”
Section: Targeted Contrast Agents For Photoacoustic Imagingmentioning
confidence: 99%
“…Zhang et al [76] performed PA imaging at 820 nm in a mouse model to evaluate the feasibility of using non-fluorescent nanodiamond as PA imaging contrast agents for effective HER2 positive breast cancer detection. Balasundaram et al [77] performed an in vivo PA imaging study with folate-conjugated polymer (CP) dots as contrast agents in xenograft mice models and they demonstrated that after 1 h of the injection of the contrast agents, the Folate-CP dots accumulated into the tumor site produced fourfold contrast-enhanced PA signal as compared to PA signals produced by CP dots.…”
Section: Exogenous Contrast Agentsmentioning
confidence: 99%